Edukasi Well Being Dan Konsep Diri Pada Lansia Di Kampung Ayapo Asei Kecil - Fenska Narly Makualaina; Fathia Fakhri Inayati Said; Crystin Evangelin Watunglawar; Nasranti Nasranti; Angela Librianty Thome (NuCSJo : Nusantara Community Service Journal, 2026)
Self-concept and well-being awareness are very important for the elderly in dealing with their health status. By having a high awareness of self-concept and well-being, the elderly can improve their ability to face health challenges, improve their quality of life, and develop their ability to deal with stress and life pressures. Well-being and Self-Concept Education for the Elderly has the goal of improving well-being and self-concept in the elderly through education and support. Problem: The elderly face problems such as declining health, social isolation, role changes, and loss of identity that can affect their well-being and self-concept. Solution: Well-being and self-concept education can help the elderly increase their awareness of the importance of health and well-being, and develop skills to cope with the changes that occur. Benefits: Well-being and self-concept education can improve the quality of life of the elderly, increase awareness about health, and develop skills to cope with changes. Strategies for well-being and self-concept education for the elderly include: Physical activity to improve health and well-being, social support to increase interaction and reduce isolation, stress management to increase self-awareness and control, and skill development to increase independence and self-efficacy. The results of well-being and self-concept education in the elderly can improve their well-being and self-concept, as well as enhance their overall quality of life.